Xerox Corporation : developing a new image - Lamb, Amanda M., (SAGE Knowledge. Cases., 2017)
After an extensive study, Xerox decided to undergo a rebranding. After unveiling a new logo, the challenge is to A) roll out the new logo, B) change perception that Xerox only makes copiers, and C) demonstrate that the rebranding was worth the multimillion dollar investment.